2016
DOI: 10.1016/j.celrep.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

A LON-ClpP Proteolytic Axis Degrades Complex I to Extinguish ROS Production in Depolarized Mitochondria

Abstract: SummaryMitochondrial dysfunction is implicated in numerous neurodegenerative disorders and in Parkinson’s disease (PD) in particular. PINK1 and Parkin gene mutations are causes of autosomal recessive PD, and these respective proteins function cooperatively to degrade depolarized mitochondria (mitophagy). It is widely assumed that impaired mitophagy causes PD, as toxic reactive oxygen species (ROS)-producing mitochondria accumulate and progressively drive neurodegeneration. Instead, we report that a LON-ClpP pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 41 publications
4
78
1
1
Order By: Relevance
“…We have recently demonstrated that mild inhibition of complex I caused by nitrite‐mediated complex I S‐nitrosation is protective in multiple models of PD and improves bioenergetic efficiency in the fibroblasts of PD patients, but not in matched controls . A protective role for mitochondrial suppression is further substantiated by other independent studies that have shown that the reversible complex I inhibitor Mitochondrial division inhibitor 1 (Mdivi‐1) is protective in PD animal models and that proteolytic degradation of complex I attenuates ROS production in damaged, depolarized mitochondria . In addition, it has been shown that fibroblasts from patients harboring mutations in the PD‐associated gene ATPase cation transporting 13A2 ( ATP13A2 ) display higher, rather than lower, mitochondrial oxygen consumption, which is in turn associated with multiple mitochondrial anomalies .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have recently demonstrated that mild inhibition of complex I caused by nitrite‐mediated complex I S‐nitrosation is protective in multiple models of PD and improves bioenergetic efficiency in the fibroblasts of PD patients, but not in matched controls . A protective role for mitochondrial suppression is further substantiated by other independent studies that have shown that the reversible complex I inhibitor Mitochondrial division inhibitor 1 (Mdivi‐1) is protective in PD animal models and that proteolytic degradation of complex I attenuates ROS production in damaged, depolarized mitochondria . In addition, it has been shown that fibroblasts from patients harboring mutations in the PD‐associated gene ATPase cation transporting 13A2 ( ATP13A2 ) display higher, rather than lower, mitochondrial oxygen consumption, which is in turn associated with multiple mitochondrial anomalies .…”
Section: Discussionmentioning
confidence: 91%
“…12 A protective role for mitochondrial suppression is further substantiated by other independent studies that have shown that the reversible complex I inhibitor Mitochondrial division inhibitor 1 (Mdivi-1) 35 is protective in PD animal models 11,13 and that proteolytic degradation of complex I attenuates ROS production in damaged, depolarized mitochondria. 36 In addition, it has been shown that fibroblasts from patients harboring mutations in the PD-associated gene ATPase cation transporting 13A2 (ATP13A2) display higher, rather than lower, mitochondrial oxygen consumption, which is in turn associated with multiple mitochondrial anomalies. 37 Together with the evidence presented in this study, these data suggest that-at least in some subtypes of PD-mitochondrial function could be an amenable target for disease modification.…”
Section: Discussionmentioning
confidence: 99%
“…Another, more intriguing possibility is that complex I is actively downregulated as a compensatory response to moderate excess generation of reactive oxygen species (ROS). Evidence of increased oxidative damage has been consistently found in the PD brain [1,45] and it has been shown that, under certain conditions, complex I inhibition [28] or modulation [29] can substantially decrease ROS generation. Irrespective of whether it is a pathogenic event or compensatory response, the extent of neuronal complex I deficiency in PD suggests that it is an important and inherent part of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the previously reported transcriptional down-regulation of the respiratory chain is at least partly driven by altered cellular composition (due to decreased number of neurons which highly express these genes) and may therefore not be the sole mechanism by which neuronal complex I deficiency occurs in PD. Indeed, it has been suggested that complex I deficiency in PD may be mediated by proteolytic degradation by the LON-ClpP protease system, rather than transcriptional regulation [30].…”
Section: Discussionmentioning
confidence: 99%